Ursolic Acid and Polydatin in Melinjo Seeds Inhibit AKT1 and GAPDH Protein and HTB-179 Cells Migration - Febriansah, Rifki; Julita, Irna (Majalah Obat Tradisional, 2024)
The incidence of lung cancer in Indonesia by 2020 has reached 34.783 cases. Melinjo contains ursolic acid and polydatin, which can suppress cell proliferation and induce cell apoptosis, respectively. This study aims to determine the Melinjo seed ethyl acetate fraction (MSEAF) ability to inhibit lung cancer proliferation and migration towards HTB-179 cells using in vitro and in silico methods. Melinjo seed powder was macerated using 70% ethanol and fractionated with ethyl acetate. The fraction obtained was then analyzed using HPLC to detect the active compounds. The compounds obtained were further analyzed using bioinformatics to determine the target proteins. The docking method was performed between ursolic acid and polydatin compounds with each target protein to determine the binding affinity. The in vitro test was done using the MTT cytotoxicity assay and scratch wound healing assay methods. The results showed that MSEAF contains ursolic acid and polydatin with retention times of 12,475 minutes and 16,564 minutes, respectively. Ursolic acid protein targets were TP53 and AKT1 with docking scores of -6,3 kcal/mol and -7,4 kcal/mol, while polydatin target proteins were GAPDH and VEGFA with docking scores of -8,8 kcal/mol and -5,5 kcal/mol. The results of the MTT assay showed an IC50 value of 35,539 g/mL, and MSEAF inhibited the migration of HTB-179 cells by slowing the migration rate. This study suggested that the MSEAF contained ursolic acid and polydatin, which exhibited the ability to prevent the growth and migration of HTB-179 lung cancer, supported by the prediction of their ability to bind to TP53 and AKT1 proteins.